Relationship between body composition and physical capacities in junior soccer players - Zanini, D.; Kuipers, A.; Somensi, I. V.; Pasqualotto, J. F.; Quevedo, J.; Teo, J. C.; Antes, D. L. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2020)
The number of studies related to soccer has been growing exponentially in the last years because the modality is considered the most popular in the world. It is known that the development of some specific physical capacities, even in young individuals, is essential to high-level performance and these capacities might be related to anthropometrics variables. The purpose of this study was to verify the relationship between body composition and physical capacities in young soccer players. Study participants were athletes from junior categories (under-12 and under-13) belonging to the Soccer Association of Chapecó, Brazil.. Athletes were submitted to agility, (Illinois), vertical jump (Sargent Jump), aerobic condition (TCAR), flexibility and sit-and-reach (Wells Bench) tests, as well as anthropometric assessment. All procedures were performed at UNOESC campus, Chapecó. Statistical analysis consisted of the Spearman`s Rô test, measuring the correlation among variables, additionally, significance level of p<0.05 was adopted. Results showed significantly correlation in agility (p=0.000; p=0.530) and vertical jump tests (p=0.003; p=-0.437) with body fat percentage. It was concluded that there is relationship between body fat percentage and agility and explosive power of lower limbs.